A political biography of Joseph Addison - Pettit, Alexander 1958- (Eighteenth-century political biographies, 2021)
One of the most durable eighteenth-century writers, Joseph Addison (1672-1719) is best remembered for his sparkling and rangy entries in the Tatler (1709-11) and the Spectator (1711-12), both co-edited with Richard Steele. This biography puts his literary career into a political context.